The economic viability of L-arginine supplementation in diets for sows in the lactation phase - RIBEIRO,Débora Virginia (2020)
ABSTRACT The objective of this study was to evaluate the economic viability of L-arginine supplementation in diets for sows during the lactation phase. A descriptive case study was carried out to identify the economic viability of the supplementation of L-arginine in the lactation ration, in relation to the control diet, on the productive performance of hyper prolific sows and their litters. The study was carried out on a commercial farm located in the state of Minas Gerais. It analyzed feasibility criteria such as the marginal physical product (MPPg) and gross margin (GM) in the scenario of technical and economic efficiency, which were compared to the GM in the control group. Technical efficiency was established at 0.71% of L-arginine in daily feed intake according to previous fieldwork by the authors, while economic efficiency obtained in this study was 0.43% supplementation. The relationship between the L-arginine price and the sale price of the piglets directly determined the economic viability, compared to the control group. Thus, initially considering the price of a piglet as R$ 9.76/kg, the cost of L-arginine should not exceed 6.61 times this value; that is, it is estimated at up to R$ 64.50. Therefore, at the final price of L-arginine of R$ 54.88, a piglet should be sold at a price of R$ 8.30/kg to make the supplementation of L-arginine in the diet of lactation-phase swine economically possible.